If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5y + -9 = 1 Reorder the terms: -9 + -5y = 1 Solving -9 + -5y = 1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -5y = 1 + 9 Combine like terms: -9 + 9 = 0 0 + -5y = 1 + 9 -5y = 1 + 9 Combine like terms: 1 + 9 = 10 -5y = 10 Divide each side by '-5'. y = -2 Simplifying y = -2
| (r-s)+(s-r)= | | 3y+2=4y+9 | | 3(3k+2)=6(4k-4) | | 5c*4e= | | 7x-60+3x+110= | | 3x+2x-6=3(2x-2) | | -a/6-7=-10 | | m-7.62=9.5 | | 4-3/8 | | 7.6a+10=78.4 | | 92=4(6m-1) | | 2y+2(y+2)= | | 7x+4=16+5x | | x/8=3;x | | -3.8=-4.1x+4.4 | | 2x+6-x=11 | | 4x-6=x+7+2x-15 | | M-23=47 | | 4x+10+27=6x | | 1/6*48 | | -3.8=4.1x+4.4 | | 12=-2.4r | | 9(10z+11)-10=269 | | Y/0.4=1.2 | | 10y^2+13y+4=0 | | 5x+4x=80 | | 5=20x-15 | | 14+2n=8 | | 5x(2x-3)-(3x-8)= | | -2(4-2)=10 | | 100=4(5-4v) | | 0.072(-63.9)(x)+0.1(2.8)+0.059(0.22)(2.8)=0 |